Transformasi Ekonomi Kepulauan Riau: Pendekatan Multisektor Untuk Penciptaan Nilai Inklusif Dan Berkelanjutan - Iman Supriadi; Rahma Ulfa Maghfiroh; Rukhul Abadi (Jurnal Archipelago, 2025)
Economic transformation in the Islands requires a comprehensive and multi-sectoral approach to create inclusive and sustainable development. This research aims to identify and analyze strategies that can drive economic growth in the islands, while ensuring inclusiveness and environmental sustainability. Descriptive qualitative analysis and case study methods were used to explore how integration between sectors can enhance the economic, social and environmental value of the islands. The results show that collaboration between the agriculture, fisheries, tourism and renewable energy sectors can create synergies that strengthen island economies. The proposed economic transformation model emphasizes local community empowerment, sustainable use of natural resources, and technological innovation. This research provides insights into how island regions can address their economic, social and environmental challenges, and offers policy recommendations for stakeholders at the local, national and international levels.